Existence of Notary Public in the Era of Digitalization - Irianto, Agung (Faculty of Law, Universitas Pekalongan, 2024)
This research describes a shift in the legal paradigm, discusses notary adaptation to information technology, and explores its impact on the substance, structure and culture of law in the context of digital economic development. The method used refers to Lawrence M. Friedman outlining the important components of the legal system: legal substance, structure and culture. The results of the research explain that the legal substance and structure are regulated in the UUJN, clarifying the authority of the Notary and offering a choice of traditional or distant notarial deeds. Gaps in regulations, including virtual implementation, pose challenges. Building a legal culture is essential to adapt to digital notary services and ensure awareness among notaries, the government, the business world and the public.